A CROSS-SECTIONAL STUDY OF PREVALENCE OF CONGENITAL ABNORMALITIES ON ROUTINE ULTRASOUND SCAN OF SECOND AND THIRD TRIMESTER PREGNANCY - Dr Kiran Kumar B.M, Dr Chandana Udayakumar, Nithyashree B, Dr shruti V dixit, Dr Divya K G, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Birth defects are a major contributor to perinatal and infant mortality, morbidity,and lifelong disability worldwide. Birth defects affect at least 3% of babies in most populations.The anomalies are the leading cause of neonatal morbidity & mortality. Defective embryogenesis or intrinsic abnormalities in the process of development result congenital anomalies. Abou